Characterization of a novel potential peptide import system in Treponema denticola. (October 2018) - Asai, Tomohiro; Okamoto-Shibayama, Kazuko; Kikuchi, Yuichiro; Ishihara, Kazuyuki
Abstract: Treponema denticola is a major etiologic agent of chronic periodontitis. On the outer sheath of T. denticola, several proteins, such as the major outer sheath protein and dentilisin were detected, and among them, a 95 kDa protein which has not yet been characterized. The aim of this study was to characterize the function of this 95 kDa protein containing gene cluster. A gene encoding this 95 kDa protein (TDE_1072) of T. denticola was inactivated by homologous recombination. We compared growth curves between the TDE_1072 mutant and wild-type strains as well as differences in gene expression by DNA microarray analysis. Differential expression of genes identified by microarray analysis was confirmed by quantitative reverse transcription-polymerase chain reaction. The proteins encoded by TDE_1072, TDE_1073, TDE_1074, TDE_1075, and TDE_1076 shared respective similarities to the substrate-binding domain (DppA) of an ABC-type dipeptide/oligopeptide/nickel transport system, and to the permease components (DppB and DppC) and ATPase components (DppD and DppF) of an ABC-type dipeptide/oligopeptide/nickel transport system. Inactivation of dppA attenuated the growth of T. denticola and dppA-dppF were co-transcribed. In contrast, expression of oppB-oppF was up-regulated in the mutant. Our findings indicate that TDE_1072 may be a potential periplasmic solute binding protein encoded by dppA that is involved in the organization of a peptide uptake system with dppB-dppF . Highlights: Treponema denticola is a major etiologic agent of chronic periodontitis. We characterized a 95 kDa protein (TDE_1072) from the outer sheath of T. denticola . The discovered TDE_1072-TDE_1076 shared similarities to DppA-DppD and DppF. dppA-dppF are co-transcribed and the operon involved in growth of T. denticola. TDE_1072 ( dppA ) may be part of a novel peptide uptake system with dppB-dppF .